The serum free triiodothyronine to free thyroxine ratio as a potential prognostic biomarker of chronic kidney disease in patients with glomerular crescents: A retrospective study - Zhang, Liwen; Wu, Yuxiao; Nie, Yuxin; Lv, Wenlv; Li, Yang; Zhu, Bowen; Jin, Shi; Shen, Ziyan; Li, Fang; Liu, Hong; Fang, Yi; Ding, Xiaoqiang (Frontiers in Endocrinology, 2022)
Background Crescent formation indicates severe glomerular pathology, and hypothyroidism usually predicts poor prognosis for severe diseases. However, the relationship between thyroid function and the progression of chronic kidney disease (CKD) is unclear. This study analysed the prognostic predictive value of the serum free triiodothyronine (FT3) to free thyroxine (FT4) ratio and its correlation with renal function in patients with CKD with crescent formation. Methods This single-centre study included 162 CKD patients with glomerular crescents confirmed by renal pathology between March 2012 and December 2014. According to the first tertile (0.284) of FT3/FT4 ratio, the patients were divided into high and low FT3/FT4 ratio groups. Kaplan-Meier and Cox regression analyses were performed to evaluate the prognostic value of the FT3/FT4 ratio. Results The age, haemoglobin, eGFR, urinary albumin-to-creatinine ratio, cardiac troponin T, N-terminal brain natriuretic peptide precursor, FT3, FT4, percentage of total crescents in non-globally sclerotic glomeruli, prevalences of hypertension, moderate to severe renal tubulopathy and crescentic nephritis, and proportion of patients receiving glucocorticoids and immunosuppressants were significantly different between high and low FT3/FT4 ratio groups (P < 0.05). Multivariate Cox regression analysis showed that when compared with patients with a high FT3/FT4 ratio (>0.284), those with intermediate and low FT3/FT4 ratios (≤0.284) had an increased risk of the long-term composite endpoint (P < 0.05 for various adjustment models). Conclusions A low FT3/FT4 ratio is associated with increased mortality and worse outcome risk in CKD patients with crescent pathology.